Overexpression of NtSOS2 From Halophyte Plant N. tangutorum Enhances Tolerance to Salt Stress in Arabidopsis - Zhu, Liming; Li, Mengjuan; Huo, Junnan; Lian, Ziming; Liu, Yuxin; Lu, Lu; Lu, Ye; Hao, Zhaodong; Shi, Jisen; Cheng, Tielong; Chen, Jinhui (Frontiers in Plant Science, 2021)
The Salt Overly Sensitive (SOS) signaling pathway is key in responding to salt stress in plants. SOS2, a central factor in this pathway, has been studied in non-halophytes such as Arabidopsis and rice, but has so far not been reported in the halophyte Nitraria tangutorum. In order to better understand how Nitraria tangutorum acquires its tolerance for a high salt environment, here, we cloned the NtSOS2 from Nitraria tangutorum, phylogenetic analyses showed that NtSOS2 is homologous to the SOS2 of Arabidopsis and rice. Gene expression profile analysis showed that NtSOS2 localizes to the cytoplasm and cell membrane and it can be induced by salt stress. Transgenesis experiments showed that exogenous expression of NtSOS2 reduces leaf mortality and improves the germination rate, biomass and root growth of Arabidopsis under salt stress. Also, exogenous expression of NtSOS2 affects the expression of ion transporter-related genes and can rescue the phenotype of sos2-1 under salt stress. All this result revealed that NtSOS2 plays an important role in plant salt stress tolerance. Our findings will be of great significance to further understand the mechanism of salt tolerance and to develop and utilize molecular knowledge gained from halophytes to improve the ecological environment.